Introduction to information systems : supporting and transforming business - Rainer, R. Kelly (Rex Kelly); Cegielski, Casey G. (Hoboken, NJ : Wiley, 2012)
"Rainer & Cegielski's new edition of Introduction to Information Systems: Enabling and Transforming Business includes updated coverage, refined cases, more illustrations, and a new "Weekly Updates" resource. Its concise chapters, many cases and examples, and online quizzing provide smooth and straightforward information and provide many hands-on activities. In general, the text is more engaging, compelling and relevant with a broader table of contents, pedagogically innovative structure, integrated activities, Excel and Access projects, and integration with WileyPLUS"--
Chapter 1 Introduction to Information Systems 1.1 Why Should I Study Information Systems?1.2 Overview of Computer-Based Information Systems1.3 How Does IT Impact Organizations?1.4 Importance of Information Systems to Society Chapter 2 Organizational Strategy, Competitive Advantage, and Information Systems2.1 Business Processes2.2 Business process reengineering and business process management2.3 Business Pressures, Organizational Responses, and Information Technology Support2.4 Competitive Advantage and Strategic Information Systems2.5 Business - Information Technology AlignmentChapter 3 Ethics and Privacy3.1 Ethical Issues3.2 PrivacyChapter 4 Information Security4.1 Introduction to Information Security4.2 Unintentional Threats to Information Systems4.3 Deliberate Threats to Information Systems4.4 What Organizations Are Doing to Protect Information Resources4.5 Information Security ControlsChapter 5 Data and Knowledge Management 5.1 Managing Data5.2 The Database Approach5.3 Database Management Systems5.4 Data Warehousing 5.5 Knowledge ManagementChapter 6 Networks 6.1 What Is a Computer Network? 6.2 Network Fundamentals 6.3 The Internet and the World Wide Web 6.4 Network ApplicationsChapter 7 E-Business and E-Commerce 7.1 Overview of E-Business and E-Commerce 7.2 Business-to-Consumer (B2C) Electronic Commerce 7.3 Business-to-Business (B2B) Electronic Commerce 7.4 Electronic Payments 7.5 Ethical and Legal Issues in E-BusinessChapter 8 Wireless, Mobile Computing, and Mobile Commerce 8.1 Wireless Technologies 8.2 Wireless Computer Networks and Internet Access 8.3 Mobile Computing and Mobile Commerce 8.4 Pervasive Computing 8.5 Wireless SecurityChapter 9 Web 2.0 and Social Networks9.1 Web 2.0 Underlying Technologies9.2 Web 2.0 Applications9.3 Categories of Web 2.0 SitesChapter 10 Information Systems within the Organization 10.1 Transaction Processing Systems 10.2 Functional Area Information Systems 10.3 Enterprise Resource Planning Systems 10.4 ReportsChapter 11 Customer Relationship Management and Supply Chain Management 11.1 Defining Customer Relationship Management 11.2 Operational Customer Relationship Management Systems 11.3 Analytical Customer Relationship Management Systems 11.4 Other Types of Customer Relationship Management Systems 11.5 Supply Chains 11.6 Supply Chain Management 11.7 Information Technology Support for Supply Chain Management Chapter 12 Business Intelligence 12.1 Managers and Decision Making 12.2 What Is Business Intelligence? 12.3 Business Intelligence Applications for Data Analysis 12.4 Business Intelligence Applications for Presenting Results 12.5 Business Intelligence in Action: Corporate Performance ManagementChapter 13 Acquiring Information Systems and Applications 13.1 Planning for and Justifying IT Applications 13.2 Strategies for Acquiring IT Applications 13.3 The Traditional Systems Development Life Cycle 13.4 Alternative Methods and Tools for Systems Development 13.5 Vendor and Software SelectionTechnology Guide 1 Hardware TG 1.1 IntroductionTG 1.2 Strategic Hardware IssuesTG 1.3 Computer HierarchyTG 1.4 Input and Output TechnologiesTG 1.5 The Central Processing Unit Technology Guide 2 Software. TG 2.1 Introduction to SoftwareTG 2.2 Software IssuesTG 2.3 Systems SoftwareTG 2.4 Application SoftwareTechnology Guide 3 Emerging Types of Enterprise Computing TG 3.1 Introduction TG 3.2 Server Farms TG 3.3 Virtualization TG 3.4 Grid Computing TG 3.5 Utility Computing TG 3.6 Cloud Computing TG 3.7 Emerging Software TrendsTechnology Guide 4 Intelligent Systems TG4.1 Introduction to Intelligent SystemsTG4.2 Expert SystemsTG4.3 Neural NetworksTG4.4 Fuzzy LogicTG4.5 Genetic AlgorithmsTG4.6 Intelligent AgentsTechnology Guide 5 Protecting Your Information Assets TG 5.1 Introduction TG 5.2 Behavioral Actions to Protect Your Information Assets TG 5.3 Computer-Based Actions to Protect Your Information AssetsGlossary. Index.
Includes index.
Keywords: Information technology; Computers / Information Technology